IMPLEMENTASI PROGRAM MUHASABAH DALAM PEMBINAAN SPIRITUAL SISWA DI MAN 3 AGAM: STUDI KUALITATIF - Erni Kasmawati; Al Athiyyah Thahirrah; Arifmiboy (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Contemporary education requires the integration of academic abilities and spiritual guidance so that students are not only intellectually superior, but also have mature religious character. Madrasahs, as Islamic educational institutions, play a strategic role in this process, but spiritual guidance in many madrasahs is still not designed and implemented systematically. This condition is also evident at MAN 3 Agam, where there is a gap in student participation in religious activities and a lack of structured planning, implementation, and evaluation related to the muhasabah program. In fact, various studies show that muhasabah, as a practice of self-introspection, is effective in increasing students' moral awareness and social behavior. This study aims to describe in depth the implementation of the muhasabah program at MAN 3 Agam through a descriptive qualitative approach, covering the process of implementation, the experiences of students and teachers, as well as supporting factors and obstacles in the field. The research results are expected to provide a contextual understanding of the dynamics of spiritual guidance in madrasahs and the contribution of muhasabah in strengthening the religious character of students.